FREQUENCY AND FACTORS INFLUENCING DELAYED PRESENTATION OF BREAST CANCER (The Research of Medical Science Review, 2024)
BACKGROUND Breast cancer is a major cause of cancer-related deaths worldwide, and early detection along with timely treatment is crucial for improving survival. However, many patients face delays in seeking care due to cultural norms, financial constraints, and limited healthcare access. Addressing these barriers is essential to support earlier diagnosis and better treatment outcomes. METHODOLOGY This study investigated the frequency and reasons behind delayed presentation in breast cancer patients at the Department of Oncology, Pakistan Institute of Medical Sciences, Islamabad, from March to September 2024. A total of 143 women, aged 18 to 70 years, were enrolled through purposive sampling. A delay was defined as waiting more than three months from noticing symptoms to consulting a healthcare provider. Data were collected using a structured questionnaire and revealed key causes of delay, including reliance on alternative treatments, perceiving symptoms as non-threatening, financial hardships, discomfort with male physicians, cultural or religious influences, traditional family norms, and limited access to healthcare. The findings highlight barriers that hinder timely breast cancer diagnosis and treatment. RESULTS Out of the 143 women, 39.9% delayed receiving breast cancer treatment by three months or so. Delays were associated with older age (p=0.025), illiteracy (p=0.006), higher socioeconomic status (p=0.011), and a family history of breast cancer (p=0.037). Main reasons were unawareness (47.4%), use of other therapeutic options (43.9%), economic problems (38.6%), and low health institute availability (29.8%). CONCLUSION The findings of current study highlight that delayed presentation for breast cancer is shaped by factors like age, education level, socioeconomic status, and family history. Challenges such as limited awareness, preference for alternative treatments, financial barriers, and restricted healthcare access highlight the need for focused efforts. Raising public awareness and enhancing healthcare services are vital to support early detection and prompt treatment.